Pengaruh Media Google Classroom terhadap Hasil Belajar Siswa Mata Pelajaran IPS Kelas VIII SMP Terpadu Ibnu Muay Babelan Bekasi - Rista, Nadia; Ubaydillah, Ubaydillah (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2021)
This study aims to determine the effect of Google Classroom Media on student learning outcomes in social studies subjects in class VIII SMP Terpadu Ibnu Muay Babelan Bekasi. The type of research conducted is quantitative. This research is ex post facto. This research was conducted in class VIII SMP Terpadu Ibnu Muay Babelan Bekasi. This research is quantitative associative with a sample size of 30 students. This data collection was carried out using the Google Classroom Media scale and documentation of even semester report cards. Validity test using content validity test (expert judgment). The reliability test uses Cronbach's Alpha which produces a reliability index of 0.968. The item correlation test is used to determine the consistency of respondents' answers. The data analysis technique was carried out by descriptive statistical analysis while to determine the relationship between the two variables, namely Google Classroom Media and student learning outcomes obtained through calculations with product moment correlation. The results showed that there was a positive and significant relationship between Google Classroom Media and student learning outcomes. Social Studies subject for class VIII of the Integrated Junior High School of Ibnu Muay Babelan Bekasi for the 2020/2021 academic year. This is indicated by the Pearson Correlation value on SPSS of 0.497 and the P value of 0.00 <0.05 which indicates a positive and significant relationship.